Implikasi Pemakaian Tiktok terhadap Psikologi Sosial Anak - Debby Sulistia, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The purpose of this study is to ascertain how utilizing Tiktok affects the behavior of kids between the ages of 7-9. Qualitative research methodology is used. Children between the ages of 7-9 made up the population of the study, which had 80 kids overall and 20 kids in the sample. the system for gathering information in numerical form and tracking children's behavior. Observation, surveys, and documentation are used as data collection tools. The validity test, normality test, linearity test, and hypothesis testing were used in the data analysis (T-test and F-test). The findings of this study indicate that the Tiktok application has a highly noticeable impact on the conduct of kids between the ages of 7-9. This is consistent with calculations made for study using the SPSS version.